PEMAHAMAN KONSUMEN TENTANG PINJAMAN ONLINE (PINJOL) DI JAKARTA - Gunawan Widjaja (Jurnal Pengabdian Kepada Masyarakat, 2022)
The level of understanding of online loan applications for people in the Jakarta area as the results obtained, respondents who have a good understanding who have income in accordance with the drinking wage, while those earning less than their drinking wages get a poor understanding and among respondents, with income above the drinking wage they have very good understanding. From these results, respondents from those who are not married, and those who are married, on average have a good understanding of online loans. The reasons for respondents choosing this online loan application are the ease of borrowing without being guaranteed, while the reasons for family support are only a few of the respondents